Seismic Behavior of Box Steel Bridge Pier with Built-In Energy Dissipation Steel Plates. (22nd October 2022) - Han, Xue; Jiang, Anlong; Zheng, Jinhuo; Zhou, Xiangui; Chen, Yewei; Fang, Sibao; Li, Xin; He, Jianhua; Li, Haifeng
Abstract : Based on the design concept of earthquake-resilient structure, a new-type of box-shaped steel piers with embedded energy-dissipating steel plates was proposed. Quasi-static tests of 6 box-shaped steel pier specimens under variable axial pressure and cyclic horizontal loading were carried out. By analyzing the failure mode, load-displacement hysteretic curve, skeleton curve, displacement ductility coefficient, stiffness degradation characteristics, strength degradation coefficient, and cumulative hysteretic energy, the effects of setting energy-dissipating steel plate, axial compression ratio, and thickness of energy dissipation steel plates on the seismic performance of new-type steel piers were discussed. Finite element models of steel bridge piers were established and compared with the test results. The analysis results using FEM agree well with the test results. Results show that the setting of energy-dissipating steel plates can effectively improve the ductility, deformation capacity, and energy-dissipating capacity of box-shaped steel piers, and effectively delay buckling deformation and cracking of wall plates. The steel plate near the bolt hole of the wall plate at the root of the new-type of box-shaped steel piers is easy to crack due to stress concentration, resulting in a rapid reduction of the maximum bearing capacity of the specimens. With the increase of axial compression ratio, the bearing capacity, energy-dissipating capacity, and earthquake-resilient capacity of the specimens increase. The smaller the thickness of the replaceable energy-dissipating steel plates, the smaller the bearing capacity and faster the stiffness degradation of the specimens become, while the ductility and energy-dissipating capacity of the specimens are improved. The axial compression ratio and the thickness of the energy-dissipating steel plate have relatively little effect on the strength degradation of the specimens. In order to facilitate the popularization and application of the new-type steel piers, formulas were also established to calculate the bearing capacity and displacement ductility factor of the new-type of box-shaped steel piers.